(untitled) (Web of Teachers: Inderscience Research, 2025)
Currently, technological changes and growing labor markets require educational institutions to equip students with both career awareness and practical competencies. This article examines the effectiveness of integrating career guidance and vocational training in secondary education. Using a conceptual and analytical framework, the study highlights how integration develops career readiness, practical skills, and adaptive competencies. The results show that such integration increases students’ motivation, aligns education with labor market requirements, and facilitates successful career choice from school.